Production and Performance of Bio-Diesel from Pongamia Oil Methyl Ester - Solaimuthu, C; Vishnu, Aryan Rajath; Azeez, Mohammed; Yadav, Naresh; Manjunath, M (International Journal of Engineering and Management Research, 2025)
Diesel engines are widely used for different applications in industrial power plant, transportation, agriculture etc. despite these advantages, environmental pollution, cost increment, depletion of crude oil becomes a major concern throughout the world. A methyl ester of pongamia was prepared and blended with diesel in four different compositions varying from 25% to 100%. Methyl esters of pongamia oils has several outstanding advantages among other new renewable and clean engine fuel alternatives and can be used in any diesel engine without modification. The engine performance and emission characteristics of pongamia bio-diesel (Pongamia Oil Methyl Ester) and its blends with petro-diesel are presented. The engine tests are conducted on a 4-Stroke Tangentially Vertical (TV1) single cylinder kirloskar engine, throughout the experiment under steady state conditions at full load condition. From the test results, it could be observed that the B25 blend gives optimum performance like higher brake thermal efficiency lower specific fuel consumption and lower emissions like lower in smoke density and oxides of nitrogen. The research findings show that B25 gives lowest emissions which make it a good alternative fuel to operate diesel locomotives without any modification in existing diesel engine.